The government centralization-decentralization debate in metropolitan areas - Hamilton, David K. (2004)
The extent of centralized or decentralized government has been an issue in America's governing system since the Revolutionary War. The major issues debated at the Constitutional Convention revolved around the amount of authority the national government should possess in relation to the states. The centraliztion-decentralization issue is still a matter of contention, but a major focus of the debate has shifted to the metropolitan area. Despite the differences in time and levels of governments, many of the same arguments made during the constitutional debates are similar to the arguments made for and against government reform in metropolitan areas today. The author reconsiders the centralization-decentralization issues debated at the Constitutional Convention and the ratification fight in the context of the current debate in metropolitan areas. Theoretical support for this exercise is provided by the inter-national relations model. An application of the issues debated and resolved by the colonists to the current debate on the extent of centralized government in metropolitan areas would favor the establishment of metropolitan government. - Reproduced.
Keywords: Centralization; Decentralization